Kegiatan mikroba di rumen dan manipulasinyauntuk mena ikkan eflsiensi f\\\'roduksi ternak - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1993)
Studies on microorganism in the role in the rumen and its activity's responses, and efforts of manipulation to increase the production efficiency of livestock were discussed to obtain steps necessary conducted Of basic data of animal growth and published microbial activities feedstuff characteristics in Indonesia, it is more likely that now is suitable to engineer strains of energy and protein yielding-microbes, use anabolic agents, and choose and treat feedstuffs in order to gain the utilisation of end product fermentation to the animal.(Keywords: Microbes, Strain engineering, Energy, Protein, Efficiency